Speckle tracking technology and investigation of risk factors for premature ventricular contraction-induced cardiomyopathy - Ma, Qiao; Zou, Beibei; Shi, Yangkai; He, Qianqian; Zhang, Muhua; Feng, Chao (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPremature ventricular contractions (PVCs) are increasingly recognized as a potentially reversible cause of cardiomyopathy, termed PVC-induced cardiomyopathy (PVCCM). Left ventricular ejection fraction (LVEF) is commonly used for diagnosis, but it lacks sensitivity for detecting early myocardial dysfunction. This study aimed to evaluate the diagnostic utility of speckle tracking echocardiography (STE)-derived strain parameters in patients with frequent PVCs and to identify associated risk factors for early myocardial impairment.MethodsA total of 258 patients with monomorphic PVCs and a PVC burden >5% on 24 h Holter monitoring were enrolled, along with 80 age- and sex-matched healthy controls. Conventional echocardiographic parameters, global longitudinal strain (GLS), and global circumferential strain (GCS) were measured. Linear regression analyses were performed to identify independent predictors of impaired strain. Subgroup analyses were conducted based on comorbidities and electrophysiological features.ResultsDespite comparable LVEF between the PVC and control groups, GLS and GCS showed attenuated magnitude in PVC patients (P < 0.001), indicating subclinical dysfunction. Regression analysis revealed that asymptomatic PVCs, paired/interpolated PVCs, wide QRS duration (≥150 ms), and higher PVC burden were significantly associated with decreased GLS and GCS magnitude. GLS and GCS showed strong inverse correlations with LVEF, particularly in patients with hypertension or prolonged QRS duration.ConclusionSTE-derived strain parameters (GLS, GCS) are more sensitive than LVEF in detecting early myocardial dysfunction in patients with frequent PVCs. Specific electrocardiographic features may help identify individuals at higher risk of strain abnormalities and could inform earlier monitoring or targeted evaluation; prospective studies are needed to establish whether intervention based on these markers prevents progression to overt PVCCM.